2008
DOI: 10.1016/j.juro.2008.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Single Port Transumbilical (E-NOTES) Donor Nephrectomy

Abstract: The initial experience with E-NOTES donor nephrectomy is encouraging. Excellent donor vascular and tissue dissection could be performed, and a quality donor kidney was retrieved transumbilically without any extra-umbilical skin incision. E-NOTES donor nephrectomy appears to have relevance and promise, especially for this typically younger, altruistic population. Natural orifices present an unprecedented opportunity for scar-free surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
172
1
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 306 publications
(187 citation statements)
references
References 9 publications
1
172
1
13
Order By: Relevance
“…The most important merit of RPS is cosmesis [3,4,6,9,11,13]. Therefore, this cosmetic merit must be retained as long as possible when performing RPS for total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most important merit of RPS is cosmesis [3,4,6,9,11,13]. Therefore, this cosmetic merit must be retained as long as possible when performing RPS for total gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, reduced port surgery (RPS), including single port surgery (SPS), in which fewer ports are used than in conventional procedures, has become increasingly popular in various surgical fields [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. There have been reports describing the application of RPS to laparoscopic sleeve gastrectomy for morbid obesity or laparoscopic partial gastrectomy for gastrointestinal stromal tumors, and the use of RPS has recently also been reported in laparoscopy-assisted distal gastrectomy for gastric cancer [1,7,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Gill et al first reported the successful completion of single-port transumbilical live-donor nephrectomy [48]. The authors used the R-Port, achieving pneumoperitoneum by inserting an additional 2-mm Veress needle port.…”
Section: Opticsmentioning
confidence: 99%
“…Living-donor nephrectomy [48][49][50] Extremely difficult Risk of prolonged warm ischemia time/ Medium Risk of complication in a healthy individual. Radical prostatectomy [54][55][56] Extremely difficult Demanding suturing.…”
Section: Lowmentioning
confidence: 99%
“…Recently, many authors, including ourselves, have successfully described the role of the laparoendoscopic single-site surgery (LESS) by umbilical approach for urological pathologies (1)(2)(3)(4). The potential benefits are related to the minimization of skin morbidity (temporary incision pain and muscle spasms, avoidance of epigastric vessel injury) and the improved cosmesis.…”
Section: Introductionmentioning
confidence: 99%